European Survey on Standards of Care in paediatric oncology centres. (July 2016) - Kowalczyk, Jerzy R.; Samardakiewicz, Marzena; Pritchard-Jones, Kathy; Ladenstein, Ruth; Essiaf, Samira; Fitzgerald, Edel; Petrarulo, Giulia; Vassal, Gilles
Abstract: Background: In recent years, the European Commission has supported an increased focus on rare cancers in order to improve quality of care, disseminate best practice and set up networks to improve access that is essential to continued progress. At European Union (EU) conference in 2009, an agreement was reached to create a 'European Standard of Care for Children with Cancer'. In 2013, the European Paediatric Oncology Society launched a Europe-wide survey in order to assess the implementation of the Standards. Methods: Representative experts from 36 countries, including 27 EU members, were invited to complete a questionnaire describing the quality of treatment and care received by young cancer patients in their country, together with the characteristics of the health care infrastructure and paediatric haematology–oncology (PHO) teams. Findings: Thirty-five European countries provided comprehensive responses. Within the responding countries, 341 PHO centres were identified. Only 18 countries consider they have full diagnostic services, all necessary drugs and supportive care. The annual incidence rate is approximately 146.1 new cancer cases/million children and adolescents. In 24 countries, paediatric haematology and oncology is officially recognised as a specific qualification. A total of 1178 specialists certified in PHO are currently working in Europe. Finally, 31 (88.6%) countries provide a multidisciplinary palliative care for terminally ill children. Interpretation: This survey provides quantitative data that demonstrate the current healthcare inequalities for children and adolescents with cancer in Europe. This variability in care provision and quality is likely to underlie the variation in childhood cancer survival rate in these countries.